PENERAPAN HAND MASSAGE TERHADAP SKALA NYERI PADA PASIEN POST OPERASI LAPARATOMI DI RS PKU MUHAMMADIYAH KARANGANYAR - Rifka Aprilia Nur Ekawati; Silvitasari, Ika; Setiyawan, Andri (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2023)
ABSTRAK Laparotomy is a treatment procedure that uses invasive methods by opening and displaying the body part to be treated. Laparoscopic patients in the world are increasing every year by 15% and the problem that often arises in post-laparotomy surgery is pain. Whereas in the number of patients with postoperative laparotomy in the Marwah room in May there were 6 patients. Based on these conditions, it is necessary to manage pain. The objective of this research is Knowing the results of the implementation of hand massage on the pain scale in postoperative laparotomy patients at PKU Muhammadiyah Karanganyar Hospital. This type of research is descriptive in the form of a case study. The approach used is nursing care approach, planning, implementation and evaluation. Respondents in this study were 2 patients with postoperative laparotomy. The instrument uses an observation sheet and a pain scale measurement questionnaire using the Numeric Rating Scale (NRS). The results of the Hand Massage implementation showed that the pain scale decreased for both respondents, for the first respondent the pain scale decreased by 5 and for the second respondent, the pain scale decreased by 4. The conclusion of this study is there are differences in the Pain Scale of postoperative Laparotomy patients after Hand Massage at PKU Muhammadiyah Karanganyar Hospital.